Laboratory Study of Local Scour Around an Array of Pile Groups in Clear-Water Scour Conditions - Ming Gong; Xinying Pan; Shengtao Du; Guoxiang Wu; Yingxue Lv; Yunjia Sun; Guangjia Ding; Bingchen Liang (Journal of Marine Science and Engineering)
Current-induced local scour around pile groups weakens the capacity of structures. In this paper, experimental tests of local scour around an array of 5 × 5 pile groups were conducted in a steady current in a hydraulic flume. The pile-to-pile space was five times the diameter of a single pile. All the tests were in clear-water scour conditions. The effects of upstream piles on the local scour characteristics of downstream piles, as well as the outer-arranged side piles on the inner-arranged piles, were studied within flow intensities of 0.37–1.0. Both the three-dimensional topography of bed elevation changes and the maximum temporal scour depths are discussed. The results showed that the minimum threshold of flow intensity that can induce local scour around the pile groups was 0.40. The scour holes were independent of each other, though a global scouring phenomenon occurred between piles at a flow intensity of 1.0. The temporal scour depths of the downstream piles increased slowly throughout the local scour processes. During the initial scouring stage, they accelerated rapidly. At flow intensities of 0.60, 0.80, and 1.0, the scour development then progressed gradually, resembling the behavior of a single pile. The developing scouring stage can hardly be distinguished in the case of flow intensity of 0.80. The maximum scour depths in the flow intensity of 0.60 showed irregular variations with increasing row and column numbers. The equilibrium scour depths in the central-positioned piles tended to a constant value of 0.5 times the pile diameter. In larger flow intensities of 0.80 and 1.0, they decreased linearly with pile row number, with the maximum scour depths at the piles in the first row. The local scour depths of the inner-positioned piles in the parallel arrangement showed few differences at the front and rear piles.